Immunomodulatory placental‐expanded, mesenchymal stromal cells improve muscle function following hip arthroplasty - Tobias Winkler; Carsten Perka; Philipp vonRoth; Alison N. Agres; Henning Plage; Bernd Preininger; Matthias Pumberger; Sven Geissler; Esther Lukasiewicz Hagai; Racheli Ofir; Lena Pinzur; Eli Eyal; et al. (Wiley, 2018)
Abstract Background No regenerative approach has thus far been shown to be effective in skeletal muscle injuries, despite their high frequency and associated functional deficits. We sought to address surgical trauma‐related muscle injuries using local intraoperative application of allogeneic placenta‐derived, mesenchymal‐like adherent cells (PLX‐PAD), using hip arthroplasty as a standardized injury model, because of the high regenerative and immunomodulatory potency of this cell type. Methods Our pilot phase I/IIa study was prospective, randomized, double blind, and placebo‐controlled. Twenty patients undergoing hip arthroplasty via a direct lateral approach received an injection of 3.0 × 108 (300 M, n = 6) or 1.5 × 108 (150 M, n = 7) PLX‐PAD or a placebo (n = 7) into the injured gluteus medius muscles. Results We did not observe any relevant PLX‐PAD‐related adverse events at the 2‐year follow‐up. Improved gluteus medius strength was noted as early as Week 6 in the treatment‐groups. Surprisingly, until Week 26, the low‐dose group outperformed the high‐dose group and reached significantly improved strength compared with placebo [150 M vs. placebo: P = 0.007 (baseline adjusted; 95% confidence interval 7.6, 43.9); preoperative baseline values mean ± SE: placebo: 24.4 ± 6.7 Nm, 150 M: 27.3 ± 5.6 Nm], mirrored by an increase in muscle volume [150 M vs. placebo: P = 0.004 (baseline adjusted; 95% confidence interval 6.0, 30.0); preoperative baseline values GM volume: placebo: 211.9 ± 15.3 cm3, 150 M: 237.4 ± 27.2 cm3]. Histology indicated accelerated healing after cell therapy. Biomarker studies revealed that low‐dose treatment reduced the surgery‐related immunological stress reaction more than high‐dose treatment (exemplarily: CD16+ NK cells: Day 1 P = 0.06 vs. placebo, P = 0.07 vs. 150 M; CD4+ T‐cells: Day 1 P = 0.04 vs. placebo, P = 0.08 vs. 150 M). Signs of late‐onset immune reactivity after high‐dose treatment corresponded to reduced functional improvement. Conclusions Allogeneic PLX‐PAD therapy improved strength and volume of injured skeletal muscle with a reasonable safety profile. Outcomes could be positively correlated with the modulation of early postoperative stress‐related immunological reactions.